The Influence of Social Media Marketing Instagram and Electronic Word of Mouth TripAdvisor on Purchase Interest at The Stones, Legian-Bali - Ciptasari, Dila Ayu; Pitanatri, Diah Sastri; Adinda, Clearesta (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
The purpose of this research is to identify the influence of social media marketing Instagram and electronic word of mouth TripAdvisor on purchase intention. The population in this research involves 100 respondents who have not had the chance to stay at The Stones Hotel, Legian - Bali. The type of information used in this research is quantitative information. This research uses primary information in the form of a questionnaire. The illustration collection method used is non-probability sampling. The analysis procedure uses multiple linear regression with SPSS version 25 for Windows. The results of this research prove that Social Media Marketing Instagram (X1) partially has a positive and significant effect on Purchase Intention with a calculated t> t table value = 3, 685> 1,660 and a significance value & ???? = 0,000 & 0.05. Electronic Word of Mouth TripAdvisor (X2) partially has a positive and significant effect on purchase intention with a calculated t> t table value = 4.525> 1,660 and a significance value & ???? = 0,000 & 0.05. Social Media Marketing Instagram and Electronic Word of Mouth TripAdvisor simultaneously have a positive and significant effect on Purchase Intention with a value of Fcount Ftable = 58.693 <3.94 and a significance value & ∝ = 0.000 & 0.05. Thus, it can be concluded that the results of this study prove that Social Media Marketing Instagram and Electronic Word of Mouth TripAdvisor have a positive and significant effect on purchase attention, and simultaneously have an effect on purchase interest.